77. The Gabbs Magnesite-Brucite Deposit, Dye County, Nevada - John H. Schilling (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
The Gabbs magnesite-brucite deposit is unique in size and is one of two magnesite deposits being exploited in the United States. It is near the town of Gabbs, which is one hundred miles southeast of Reno, in west-central Nevada. The brucite was discovered in 1927; the magnesite was found while exploring the brucite. During World War II, more than 80,000 tons of magnesium metal was produced from about 900,000 tons of magnesite ore mined from these deposits. An additional 5,000,000 tons of magnesite and 1,000,000 tons of brucite have been produced for use in making magnesia refractories and chemicals. Basic Inc., presently the only producer, mines 1.5 ± 0.25 million tons of ore and waste annually using high-selective open-pit rriethods; the ore is up-graded, calcined, and processed into a variety of products. Known reserves of highgrade (less than 5 per cent CaO) magnesite ore total more than 25,000,000 tons, and there are larger tonnages of lower-grade material; brucite reserves are small. The magnesite and brucite are in generally west-dipping dolomite of the upper member of the late Triassic Luning Formation, in the over-riding plate of the Paradise thrust fault. A great variety of dikes and a stock of Cretaceous granodiorite intrude the Luning Formation in the vicinity of the magnesite-brucite deposit. The magnesite bodies are scattered over an area of about a square mile around a prong of granodiorite which extends north from the stock. The brucite is mainly in two bodies in contact with the prong of granodiorite; at the surface and along deeper cracks the brucite has weathered to hydromagnesite and artinite. In the area of magnesite-brucite mineralization, much of the dark, fine-grained, schistose, regionally-metamorphosed dolomite of the Luning Formation has been marmorized to a lighter-colored, coarser-grained, massive dolomite that is intergrown in varying proportions with the magnesite. The magnesite and marmorized dolomite can not be distinguished visually. In addition to the two varieties of dolomite, the gangue in the magnesite and brucite bodies mainly is the various varieties of dike rock, serpentine and a variety of other "contact" minerals, and "post-ore" dolomite and calcite. The magnesite ( and recrystallized dolomite) is believed to have formed by the hydrothermal replacement of the regionally metamorphosed sedimentary dolomite; alternatively it has been suggested that the magnesite is sedimentarv and formed contemporaneously with the dolomite in an embayment of the Triassic sea. Because all the igneous rocks exposed in the immediate vicinity of the magnesite deposits appear to be younger than the magnesite, the ore-forming solutions are thought to be related to a somewhat older granite which crops out elsewhere in the area. The brucite is the result of contact-metasomatic replacement of magnesite during the emplacement of the granodiorite stock.